Typical Shape Differences in the Subtalar Joint Bones Between Subjects with Chronic Ankle Instability and Controls - Tümer, Nazlı (J Orthop Res, 2019)
Bone shapes, particularly those defining the subtalar joint (STJ), have not received much attention yet as a risk factor for developing chronic ankle instability (CAI) after sustaining a lateral ankle sprain (LAS). This study aimed to compare three‐dimensional (3D) shape variations in the STJ bones within individuals with CAI and healthy controls. 3D statistical shape models (SSMs) of the STJ bones were built to describe the bone shape variations observed within a population consisting of 26 individuals with unilateral CAI and 26 healthy controls. Using the SSMs and analysis of covariance test, age‐ and gender‐adjusted shape variations in the bones were compared within individuals with CAI and healthy controls. The mean age of the CAI patients (14 males and 12 females) and healthy controls (12 males and 14 females) was 29 (standard deviation [SD] = 11) and 36 years (SD = 11), respectively. Tali and calcanei did not significantly vary between ipsilateral CAI and their contralateral ankle. Two shape modes, one for the talus (p = 0.015, variations in the curvature of the talar lateral process and the inclination angle of the talar neck relative to the body) and one for the calcaneus (p = 0.003, variations in the medial and lateral tuberosities, and the contour of the anterior articular surface), described significant shape differences between the CAI patients and healthy controls. The CAI patients generally had flatter talar joint surfaces and a flattened calcaneal ground‐contact surface. These findings suggest that specific bone shapes may increase the risk of developing CAI after sustaining a LAS. © 2019 The Authors. Journal of Orthopaedic Research(®) Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 37:1892–1902, 2019